Peran Akuntan Forensik Sebagai Upaya Penegakan Hukum Pada Kejahatan Fraud (Penggelapan) di Perusahaan Kelapa Sawit - Rahmatsyah, Rahmatsyah (Fakultas Syariah INSURI Ponorogo, 2022)
Palm oil is one of the commodities to improve Indonesian economy. However, in palm oil companies, fraud often occurs which is detrimental to the company. One of the frauds committed by employees is embezzlement of funds. Therefore, an analysis is needed to prevent and overcome the problem of embezzlement of funds in oil palm companies. The purpose of this research is 1) to find out the juridical rules of embezzlement of funds in private companies, 2) to find out the role of forensic accounting in tackling embezzlement crimes, 3) to find out the obstacles for forensic accountants in carrying out the duties in the enforcement of embezzlement crimes. This research was conducted with a normative juridical approach. Results of the study 1) embezzlement is one of the frauds that can be charged using Article 372 of the Criminal Code, 2) forensic accountants are very useful for tracing budgets that have been embezzled by employees in office, forensic accounting is also useful for preventing other frauds not only embezzlement in palm oil companies, 3) the obstacle for forensic accountants in carrying out law enforcement is having to deal with people who are involved in fraudulent treatment which will always hinder when an investigative audit of the fraud is carried out. Recommendation: it is necessary to anticipate fraud, including embezzlement by hiring the services of a forensic accountant so that all company assets can be secured